Marital Satisfaction: An Analysis of Long Distance Marriage Couples - Bramana Nanditya Putra; Afdal Afdal (Universitas Negeri Padang, 2020)
This research aims to describe marital satisfaction of long distance marriage and and the difference marital satisfaction between husband and wife undergoing long-distance marriages(LDM). . This research was a comparative research with a sample number of 45 couples who have LDM. Sample collection withdrawal technique using a purposive sampling technique. This research was measured using a Marital Satisfaction Inventory developed from ENRICH Marital Satisfaction Scale with a few adjustments. The research findings reveal that: (1) marital satisfaction of husband undergoing long-distance marriages is generally in medium category with a percentage of 70.25%, (2) marital satisfaction of wives undergoing LDM is generally in the high category with a percentage of 74.65%, and (3) there is no difference in marital satisfaction between husband and wife undergoing LDM with the value F of 4,940 with probability 0.029 smaller than 0.05.